OPERATING LEVERAGE DAN RISIKO SISTEMATIK PERUSAHAAN - Yulianti, Retno (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2006)
Abstract   The objective of this research is to test the effect of operating leverage to the firm’s market risk. The market risk is the risk that relation with the firm’s stock price. This research employed homogenous sample that is 33 firms included in chemical basic industry from 1994 to 2002. This research used regression analysis. The research findings prove that there is no effect of operating leverage to the firm’s market risk. Keywords: operating leverage, systematic risk.